2001
DOI: 10.1634/theoncologist.6-2004-32
|View full text |Cite
|
Sign up to set email alerts
|

The Vascular Endothelial Growth Factor (VEGF) Signaling Pathway: A Therapeutic Target in Patients with Hematologic Malignancies

Abstract: Angiogenesis is an important component in the progression and metastasis of solid tumors. We now appreciate that angiogenesis is also critically involved in the pathogenesis of hematologic malignancies. Current data suggest important prognostic and therapeutic implications of angiogenesis in a variety of malignancies of the hematopoietic system, including acute and chronic leukemias, myeloproliferative diseases, multiple myeloma, non-Hodgkin's lymphomas, and Hodgkin's disease. Vascular endothelial growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Vascular endothelial growth factor (VEGF) is a key angiogenic factor that regulates several endothelial cell functions, particularly mitogenesis. It was shown that the levels of VEGF in association with poor prognosis is raised in hematologic malignancies (Giles, 2001).…”
Section: Inhibition Of Vegf/hsp27 Signaling Pathwaymentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is a key angiogenic factor that regulates several endothelial cell functions, particularly mitogenesis. It was shown that the levels of VEGF in association with poor prognosis is raised in hematologic malignancies (Giles, 2001).…”
Section: Inhibition Of Vegf/hsp27 Signaling Pathwaymentioning
confidence: 99%
“…Angiogenesis, the process resulting in the formation of new blood vessels from pre-existing ones, plays an important role in the development and destabilisation of atherosclerotic plaques [6][7][8]. Vascular endothelial growth factor (VEGF) has been shown to be the most important pro-angiogenic growth factor in humans [9][10][11] exerting its angiogenic effects by stimulating VEGF receptor 2 (VEGFR-2), which is critical for promoting proliferation and differentiation of endothelial cells [11,12]. Indeed, it has been demonstrated directly that VEGF drives the growth of existing plaques in high fat diet-fed New Zealand White rabbits and hypercholesteraemic ApoE −/− mice [13,14].…”
mentioning
confidence: 99%
“…VEGF expression in many solid tumors has been shown to be a marker of poor prognosis including breast, renal, oropharyngeal, colon, gastric, and lung cancers (10)(11)(12)(13)(14)(15). Several recent reports have implicated VEGF as a powerful prognostic indicator in many hematologic malignancies as well as acute (16) and chronic myeloid leukemia (17), chronic lymphocytic leukemia (18), non-Hodgkin's lymphoma (19), Hodgkin's disease (20), and myelodysplastic syndromes (21).…”
mentioning
confidence: 99%